An Insight on Machine Learning Algorithms for Predicting Heart Diseases (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Heart Disease (HD) is one among the critical diseases that severely affects the human kind. The presence of heart disease arise insufficient blood supply to other body parts. Henceforth, diagnosing the HD on time prevents the heart failure. Traditional diagnosing procedure regarding HD detection and prediction becomes unreliable in many circumstances. Recent studies put forth the witness that implication of Machine Learning (ML) in traditional HD detection and prediction has resulted in superior performance. Further, Computer Aided Diagnosis using one-dimensional and multi-dimensional signals assists in diagnosing the HDs at an early stage, thereby saving the human life. The objective of this manuscript is to present an overview of HDs, symptoms and role of ML in HD predictions followed by various state-of-the-art ML algorithms that aids in identification and prediction of HD at an early stage to save the human life;